2014
DOI: 10.1158/1541-7786.mcr-13-0642
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating TBK1 as a Therapeutic Target in Cancers with Activated IRF3

Abstract: TBK1 (TANK-binding kinase 1) is a noncanonical IkB protein kinase that phosphorylates and activates downstream targets such as IRF3 and c-Rel and, mediates NF-kB activation in cancer. Previous reports demonstrated synthetic lethality of TBK1 with mutant KRAS in non-small cell lung cancer (NSCLC); thus, TBK1 could be a novel target for treatment of KRAS-mutant NSCLC. Here, the effect of TBK1 on proliferation in a panel of cancer cells by both genetic and pharmacologic approaches was evaluated. In KRAS-mutant ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 36 publications
3
38
0
Order By: Relevance
“…Although the protein kinase STK33 was initially proposed to be a druggable target in KRAS -mutant cells 144 , subsequent studies found that neither genetic or pharmacologic inhibition of STK33 selectively inhibited the growth of such cells 162 . Genetic and pharmacologic evaluations of TBK1 found no consistent requirement for TBK1 in the growth of KRAS -mutant tumour cell lines in vitro 163 , although combined TBK1 and MEK inhibition led to partial regression of Kras;p53 mutant lung tumours in mice 164 . This result highlights a limitation of high throughput screening - hits must be rigorously validated.…”
Section: Synthetic Lethal Interactors Of Mutant Ras – Needles In the mentioning
confidence: 99%
“…Although the protein kinase STK33 was initially proposed to be a druggable target in KRAS -mutant cells 144 , subsequent studies found that neither genetic or pharmacologic inhibition of STK33 selectively inhibited the growth of such cells 162 . Genetic and pharmacologic evaluations of TBK1 found no consistent requirement for TBK1 in the growth of KRAS -mutant tumour cell lines in vitro 163 , although combined TBK1 and MEK inhibition led to partial regression of Kras;p53 mutant lung tumours in mice 164 . This result highlights a limitation of high throughput screening - hits must be rigorously validated.…”
Section: Synthetic Lethal Interactors Of Mutant Ras – Needles In the mentioning
confidence: 99%
“…Therefore, it was very intriguing when TBK1 was identified as a synthetic lethal interactor of mutant KRAS (Barbie et al 2009). However, subsequent studies found that TBK1 function was not tightly linked with RAS -mutant cancer (Muvaffak et al 2014). Another effector implicated in RALB-dependent PDAC invasion is RALBP1/RLIP76 (Neel et al 2012), a multidomain protein that can act as a GTP-activating protein (GAP) for the Cdc42 and RAC1 RHO family small GTPases.…”
Section: Targeting Kras: Do Effector Inhibitors Hold the Greatest Promentioning
confidence: 99%
“…RalB binding to Sec5 leads to an interaction of Sec5 with TBK1, a protein kinase known to regulate NF-κB signaling. Intriguingly, TBK1 has recently been identified in siRNA screens as a synthetic lethal partner of activated K-Ras [62], although a subsequent study failed to support this relationship [63]. …”
Section: Ral Effectorsmentioning
confidence: 99%